Impact of BRAC on community health networks: a village study - Begum, Shamim Ara; Hannan, Rowshan; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2019)
Mere health service provision may be unable to bring about the desired impacts on health outcomes. Such outcome impact is mediated by changes in health seeking behavior underpinned by changes in health kr!Owledge, attitude and practice---variables which are socially embedded and transmitted through networks. BRAC, the largest national NGO in the world, in an effort to provide cost-effective and mass scale essential health service coverage in rural areas, makes use of locally recruited community health workers-shasthya shebikas. This study attempts to describe the health network in a village where the shebika has been working for many years. It has tried to assess the past health network in the village and how the introduction of a shebika has influenced this network. It also examines the power and influence of the shebikas in a village, and how this influence has changed over time. The study finds that far from polarising the village between members and non-members the shebikas are actually consulted by a range of people. Thus it can be said that the health network in the village, which is dominated by the shebikas have created an inclusive health network of different NGO and non-NGO members. After ten years of BRAC's Mainstream Health Programme in the study village we found that the shebikas reached a large and inclusive group transcending social and wealth categories. This is even more encouraging in view of the fact that the shebikas come from the lowest wealth category. Though only six percent of the households did not visit any health practitioner at all, they were noted to include some of the poorest in the village, suffering from exclusion from multiple networks. Future research should explore the pathways through which such exclusions happen and the general interlinkages between health and other socio-economic networks.